HUBUNGAN ASUPAN PROTEIN DENGAN STATUS GIZI PADA REMAJA PUTRI DI PONDOK PESANTREN, KABUPATEN TUBAN - Kusma Ristanti, Idcha; Ainun Nafies, Dian Ayu; Prasiwi, Nikita Welandha; Lailiyah, Ella Janatul (STIKes Mitra Keluarga, 2024)
Introduction : Nutritional problems are health problems that can occur at all ages. Adolescents are one of the groups that easily experience nutritional problems. Nutritional status is a description of the body's condition as a result of the utilization of nutrients from food consumed daily. One of the nutrients, protein, is an important nutrient for growth, repair, maintenance of body tissues and maintaining physiological balance. The aim of this research was to investigate the correlation between protein consumption and nutritional status among teenage girls. Method: This was an analytic research with a cross sectional approach. The sample of this study was 200 female students of islamic boarding school, aged 15-19 years old. Independent variable of protein intake was collected using Recall-24 hour method, dependent variable of nutritional status was measured based on IMT/U indicator, and analyzed statistically with spearman correlation. Result: The results of spearman correlation test showed a p-value=0.000 for the relationship between protein intake and the nutritional status of adolescent girls, there was a tendency for respondents with more protein intake to overweight, while respondents with normal protein intake have normal nutritional status. Conclusion: Protein intake affects nutritional status, the higher the protein intake, the higher the risk of overweight. Suggestions for further research could involve studying the improvement of knowledge and skills of pesantren administrators in preparing balanced nutritional meals for students.